Investigations of User Positioning Errors by Using Local DFMC SBAS Correction with Higher-Order Ionospheric Delay Mitigation in Thailand - Sophan, Somkit; Supnithi, Pornchai; Myint, Lin M.M. (My University, 2024)
Dual-frequency multi-constellation (DFMC) satellite-based augmentation system (SBAS) is essential to support airplane navigation. Typically, the global navigation satellite system (GNSS) with the L1 (1575.42 MHz) and L5 (1176.45 MHz) frequencies are utilized to remove the ionospheric delays based on the ionosphere-free (IF) combination (L1-L5), nevertheless, the errors due to higher-order ionospheric (HOI) delays still need to be corrected. With the local DFMC SBAS correction with a HOI mitigation in Thailand had not been considered and investigated yet. Therefore, we investigate local DFMC SBAS corrections with the HOI mitigation which are generated from the base stations in Thailand. The corrections are approximated from the local total electron content (TEC) values based on the Klobuchar model. Firstly, the local HOI days are estimated by using the observed pseudorange, and consequently, the local DFMC SBAS corrections are generated based on the minimum sum-variance technique with the IF carrier smoothing code. The GPS, Galileo, and QZSS data from the reference stations network in Thailand are utilized. In the preliminary study, the user positioning errors on the quiet days are evaluated based on the single point positioning (SPP) algorithm. The results show that both horizontal and vertical position errors are reduced by the local DFMC SBAS corrections with the HOI mitigation. The position error improvements on the quiet days can be experienced by 11%.
Keywords: DFMC SBAS; GNSS; Higher-order ionospheric delay; SPP